PRODUKSI GULA DARI HIDROLISIS PATI SINGKONG MENGGUNAKAN ENZIM GLUKOAMILASE HASIL FERMENTASI SUBSTRAT PADAT OLEH ASPERGILLLUS AWAMORI PADA MEDIUM WHEAT BRAN DAN SUMBER KARBON TAMBAHAN - Fathimah Azzahra, Azkia
Sugar is one of basic needs for Indonesian people. Sugar is used as sweetener or as additive in food and beverage industry. Many food and beverage industries is starting to use glucose syrup as sugar sources. The basic ingredients in producing glucose can be obtained from materials containing polysaccharides such as from starch through the hydrolysis process. Cassava is a plant that contains high amount of starch. The process of hydrolysis of cassava starch into glucose can be done through a chemical process or through an enzymatic process. The enzymatic hydrolysis process is considered to be better because it is more environmentally friendly. Glucoamylase is an enzyme used in the starch hydrolysis process. Optimization of the fermentation process in the production of enzymes is done to increase the activity of the enzymes. The objective of this research is to determine the activity of the crude glucoamylase enzyme from solid substrate fermentation (SSF) on wheat bran medium with additional carbon sources in the form of glucose and starch at different fermentation times (24, 48, 72, 96, and 120 hours), to determine the dextrose equivalent (DE) value of the enzymatic hydrolysis process of cassava starch into glucose, and to determine the Michaelis-Menten kinetic parameters using the line-weaver burk curve for the enzyme with the highest activity. The highest glucoamylase enzyme activity was obtained at a fermentation time of 96 hours with the activity values for the variation of control, additional carbon sources of glucose, and starch were 1017.28 U/mL, 651.47 U/mL, and 1197.83 U/mL, respectively. Glucose filtrate in the variation of control, additional carbon sources of glucose, and starch had DE values of 52.38, 49.10 and 56.88%, respectively. The values of Km and Vmax obtained from the Lineweaver-Burk equation are 0.57% and 1428.57 U/mL, respectively.